Short-term fasting enhances the resistance of common carp (Cyprinus carpio) to Aeromonas hydrophila: Impacts on gut microbiota, glucose, and oxidative stress - Dahliatul Qosimah; Tiara Widyaputri; Muhamad Firman Ataullah; Syifa Fu’ada; Zackya Najib; Atsir Farhan; Fathia Zahra Aulia Putri; Anggieta Ratuyustiarany (Veterinary World)
Background and Aim: Aeromonas hydrophila is a significant pathogen in freshwater aquaculture, contributing to high morbidity and mortality in common carp (Cyprinus carpio). Conventional reliance on antibiotics raises concerns about resistance and environmental impact. This study aimed to evaluate the effects of short-term fasting (1 or 2 days) on physiological, oxidative stress, and microbial responses in C. carpio infected with A. hydrophila.